Nonlinear Optical Properties and Temperature‐Dependent UV–Vis Absorption and Photoluminescence Emission in 2D Hexagonal Boron Nitride Nanosheets. Issue 6 (22nd January 2015) - Kumbhakar, Pathik; Kole, Arup Kanti; Tiwary, Chandra Sekhar; Biswas, Subrata; Vinod, Soumya; Taha‐Tijerina, Jaime; Chatterjee, Udit; Ajayan, Pulickel M.
<x xml:space="preserve">Abstract</x> Recently, a lot of interest has been centred on the optical properties of hexagonal boron nitride (h‐BN), which has a similar lattice structure to graphene. Interestingly, h‐BN has a wide bandgap and is biocompatible, so it has potential applications in multiphoton bioimaging, if it can exhibit large nonlinear optical (NLO) properties. However, extensive investigation into the NLO properties of h‐BN have not been done so far. Here, NLO properties of 2D h‐BN nanosheets (BNNS) are reported for the first time, using 1064‐nm NIR laser radiation with a pulse duration of 10 ns using the Z‐scan technique. The reverse saturable absorption occurs in aqueous colloidal solutions of BNNS with a very large two‐photon absorption cross section (σ2PA) of ≈57 × 10−46 cm4 s−1 photon−1. Also, by using UV–Vis absorption spectroscopy, the temperature coefficient of the bandgap (dEg/dT) of BNNS is determined to be 5.9 meV K−1. Further defect‐induced photoluminescence emission in the UV region is obtained in the 283–303 K temperature range, under excitations of different wavelengths. The present report of large σ2PA combined with stability and biocompatibility could open up new possibilities for the application of BNNS as a potential optical material for multiphoton bioimaging and advanced photonic devices.